Immune check point inhibitors for ocular adnexal and periocular tumors - Palwasha Syar; Sara Moussavi; Carlos Torres-Caballa; Bita Esmaeli (Taiwan Journal of Ophthalmology)
The introduction of immune checkpoint inhibitors (ICIs) into clinical medicine has resulted in more robust response rates for various malignancies, including metastatic and locally advanced periocular and ocular tumors. Their increased utility constitutes a pivotal shift from invasive surgical treatments allowing patients to proceed with eye preserving therapies while also achieving local and metastatic tumor control. The aim of this review article is to provide a summary and updates on the current clinical utility of ICIs for conjunctival and periocular melanoma and squamous cell carcinoma, periocular Merkel cell carcinoma and periocular basal cell carcinoma resistant to BRAF inhibitors. A literature search was conducted on PubMed of programmed cell death protein 1 (nivolumab, pembrolizumab), PD-L1 (atezolizumab, avelumab, durvalumab), and CTLA-4 inhibitors (ipilimumab, tremelimumab) along with previously noted conjunctival and periocular tumors. While this article references several large clinical trials for cutaneous tumors, most of the ocular data are limited to case reports and series. Our overall review presents promising results with the usage of ICI for patients, noting an increased overall survival rate, clinical control of local and metastatic disease and decreased surgical morbidity, while avoiding orbital exenteration. These improvements have not come without considerations for adverse immune-related side effects and clinicians needs to be judicious is deciding between the overall efficacy and side effects.